French Suites for the Piano, Volume 19 - BACH, Johann Sebastian (G. Schirmer. Inc., 1896)
Di dalam buku ini terdapat lagu: Suite 1, D-minor; Suite 2, C-minor; Suite 3, B-minor; Suite 4, Eb-minor; Suite 5, G-minor; Suite 6, E-major